The Influence of the Implementation of Business Ethics on the Sustainability of Candikuning Traditional Market Traders - Indrianisa, Nur Laili; Arisena, Gede Mekse Korri (Universitas Indo Global Mandiri Palembang, 2025)
Objective: Business ethics play an essential role in forming patterns and transaction systems of a business, which ultimately determines the fate of a business run by a person. This study aims to identify the characteristics of traders, identify the description of the application of Islamic business ethics of traders, and see and analyze the effect of the application of Islamic business ethics on the success of Candikuning traditional market traders. Design/Methods/Approach: The research sample was taken from as many as 71 respondents using a random sampling technique selected using the Slovin formula with a 5% error balance. The data analysis method uses qualitative descriptive analysis, class interval analysis, and multiple linear regression analysis with software tools, namely SmartPLS 4.0. Findings: The results of the study show that management ethics, marketing ethics, business environmental ethics, and sustainable environmental ethics have a significant effect on business blessings, which in turn have a positive impact on financial growth, customer growth, and growth and learning. Business actors must develop and implement business ethics and focus on maintaining business blessings by prioritizing sustainability in various aspects of the business to create a strong foundation for growth and customer loyalty, build a positive image, and improve business performance. Originality/Value: The novelty of the research is to see how much influence the application of management ethics, marketing ethics, business environmental ethics, and sustainable environmental ethics affects the blessing of the business, which will then affect financial growth, customer growth, growth and learning of traditional market traders in Candikuning. Practical/Policy implication: The findings of this study have significant implications for the practice of business ethics by following Islamic law which will affect the success of the business. These implications highlight the relevance of research in the real world.